Instrumented triple single-leg hop test: A validated method for ambulatory measurement of ankle and knee angles using inertial sensors. (December 2020) - Ahmadian, Niloufar; Nazarahari, Milad; Whittaker, Jackie L.; Rouhani, Hossein
Abstract: Background: Hop tests are commonly used in clinical environments to measure function after sport-related knee injuries. Joint angle measurement during hopping is feasible in research-based environments equipped with motion-capture systems. Employing these systems in clinical research settings is inefficient, given the associated cost, preparation time, and expertise required to administer and interpret the findings. Therefore, this study aimed to introduce a wearable system comprising three inertial measurement units for 3D joint angular measurement during horizontal hop tests, validate the joint angles against a camera-based system, and evaluate its applicability in clinical research environments. Methods: Ten able-bodied participants were outfitted with three inertial measurement units during triple single-leg hop trials. 3D knee and ankle angles were calculated using the strap-down integration method, and results were compared with camera-based joint angles. Additionally, knee and ankle range of motions (RoMs) during bilateral triple single-leg hop trials were compared for 22 participants with unilateral sport-related knee injuries and 10 uninjured participants. Findings: Estimated angles had root-mean-square and RoM error medians of less than 2.3 and 3.2 degrees for both joints, and correlation coefficients of above 0.92 when compared with the camera-based system, for all hop phases. Injured participants had smaller sagittal ankle RoM ( P  = .008) on their injured side, during the third hop. Concurrently, they demonstrated smaller knee RoM symmetry indices ( P  = .017) and injured knee sagittal RoMs ( P  = .009) compared to uninjured participants. Interpretation: The introduced system had appropriate accuracy to highlight post-injury modifications in hopping kinematics and reveal noteworthy differences in RoM of clinical samples. Highlights: 3 inertial measurement units per limb can estimate knee and ankle angles along hops. Median errors of 3D joint angles along triple single-leg hop were about 3 degrees. 3rd hop ankle angles revealed side-to-side differences for a group with knee injury. 3rd hop knee angles showed differences among injured and uninjured clinical groups. The validated wearable system can highlight hopping alterations post knee injuries.